DINAMIKA METODOLOGI USHUL FIKIH: ANALISIS KRITIS TERHADAP ALIRAN FUQAHĀ’, MUTAKALLIMĪN, DAN ṬARĪQAT AL-JAM‘ - Abdul Hakim (CV. Denasya Smart Publisher, 2026)
In the early period of Islam, uṣūl al-fiqh did not exist as a formally codified discipline, as the Companions and the Successors possessed strong linguistic competence and direct proximity to the sources of revelation, enabling them to intuitively comprehend principles of legal inference (istinbāṭ). However, with the expansion of the Islamic world, the gradual decline in Arabic linguistic proficiency, and the increasing complexity of ḥadīth transmission, the codification of uṣūl al-fiqh methodology became inevitable. This study aims to critically analyze the historical development of uṣūl al-fiqh methodology from the formative period to the emergence of three major methodological trends, namely Ṭarīqat al-Mutakallimīn, Ṭarīqat al-Fuqahā’, and Ṭarīqat al-Mutaʾakhkhirīn, as well as to examine the implications of these methodological differences for Islamic legal formulation. Employing a qualitative-descriptive approach with a historical-normative orientation, this research relies on library-based analysis of primary and secondary uṣūl al-fiqh sources, utilizing comparative and content analysis methods. The findings indicate that differing epistemological orientations among these methodological trends significantly influence approaches to textual evidence, hierarchies of legal reasoning, and interpretations of fundamental legal concepts such as ṣiḥḥah (validity), ijzā’ (sufficiency), and qaḍā’ (make-up obligation). This study affirms that uṣūl al-fiqh is not merely an abstract theoretical construct but a dynamic methodological framework that sustains the continuity and relevance of Islamic law in response to changing historical contexts.